Peningkatan Status Mutu Sungai Cimahi dengan Penyusunan Rencana Induk Sistem Pengolahan Air Limbah Domestik - Muhammad Viqi Rafianto; Eka Wardhani (Jurnal Serambi Engineering, 2021)
Population growth greatly influences changes in land use, and the Cimahi Watershed (DAS) is also experiencing these changes.  The change in land use has resulted in reduced water  quality in the Cimahi River. Water pollution in the Cimahi River is greatly influenced by the discharges from the Cimahi River watershed facilities. This research identifies  a master plan for wastewater management in the Cimahi watershed to improve water quality of the Cimahi River  and establishes a Domestic Wastewater Management System (SPALD) in the Cimahi Watershed region . Wastewater management provisions are regulated by PermenPUPR No. 4 of 2017 through a series of screening. As a result of a series of screenings conducted for the Cimahi watershed, which consists of seven sub-districts, only one sub-district can use the Centralized SPALD, namely Cimahi Village. Two sub-districts of the Cimahi watershed did not meet the  population density selection criteria , and five sub-districts  within the Cimahi watershed did not meet the criteria for a depth review.  Follow-up screening, such as groundwater  permeability, ability to fund , and  slope of the land for all urban villages met the screening criteria.